Gingivektomi Sebagai Perawatan Enlargement Gingiva : Laporan Kasus - Karyadi, Edi; Widodo, Aisha Farrachan (Bhakta Dental Journal, 2025)
Background: Gingival enlargement is a pathological condition characterized by excessive growth of the gingiva. Objective: To describe a case of gingival enlargement treated with a gingivectomy procedure. Case report: A 67-year-old woman came to Soelastri General Hospital complaining of enlarged gums. The complaint had been felt for 1 month. The patient complained that her upper right gum was enlarged and often bled. Intraoral examination found gingival enlargement in region 12. The treatment plan was scaling and root planing followed by gingivectomy. Discussion: Gingival enlargement in this patient was treated with phase 1 periodontal therapy, followed by gingivectomy. Gingivectomy improves visibility and accessibility to remove superficial deposits and thoroughly smooth the roots, creating a good environment for healing and restoration of the physiological contour of the gingiva. Conclusion: Gingivectomy is a procedure to eliminate gingival enlargement and requires periodic supportive periodontal therapy to monitor for recurrence in the future.